F52 Acoustic voice features in Huntington's disease in native English, Spanish and polish speakers. (12th September 2022) - Fahed, Vitória S; Doheny, Emer P; Collazo, Carla; Krzysztofik, Joanna; Mann, Elliot; Jones, Philippa; Drew, Cheney; Witkowski, Grzegorz; Cubo, Esther; Busse, Monica; Lowery, Madeleine M; ,
Abstract : Background: Changes in voice are a characteristic symptom of Huntington's disease (HD), and can be associated with lack of motor control (dysarthria) or cognitive impairment. Objective quantitative measures of voice that can be performed within the clinic or home may provide a method to monitor disease progression and help target interventions. Aims: This study aimed to compare acoustic voice features from voice recordings in English, Spanish and Polish-speaking in people with HD and controls. Methods: Voice was recorded using mobile devices (Samsung Tablets Tab A and S6 Lite, and Smartphone Huawei Mate Lite 10) in participants with HD and matched control groups across three cohorts: English- (n=29), Spanish- (n=36) and Polish- (n=25) speaking. Voice was recorded during sustained vowel phonation (/a:/), syllable repetitions (/pa/, /ta/, /ka/, /pataka/, /pati/), and reading of a language-specific passage (English, 1 Spanish, 2 Polish 3 ). Acoustic voice features were estimated and compared across cohorts and biological sex. Statistical analysis was performed using linear mixed models. Results: Significant differences between HD and control participants were observed for the standard deviation of fundamental frequency, harmonics-to-noise ratio, jitter and shimmer ( Figure 1 ). Effect of biological sex was observed on all features examined. Conclusions: The results illustrate differences between HD and control participants, consistent across languages, suggesting an opportunity to develop a language-agnostic protocol (sustained vowel and syllable repetition) that can be implemented using mobile devices to evaluate voice impairment in HD. References: Patel et al . 2018. Orozco-Arroyave et al . 2016. Pettorino et al . 2017.